2007
DOI: 10.1007/s00726-006-0405-z
|View full text |Cite
|
Sign up to set email alerts
|

Taurine reduces caspase-8 and caspase-9 expression induced by ischemia in the mouse hypothalamic nuclei

Abstract: Taurine is a sulphur-containing amino acid abundant in the nervous system. It protects cells from ischemia-induced apoptosis, but the mechanism underlying this is not well established. The aim of our study was to explore the effects of taurine on two main pathways of apoptosis induced by ischemia: receptor-mediated and mitochondrial cell death. Brain slices containing the supraoptic (SON) and paraventricular (PVN) nuclei of the hypothalamus were incubated in vitro under control and simulated ischemic (oxygen-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…The mechanisms involved on its actions range from increasing insulin secretion (Ribeiro et al 2009) and action ), in diabetes; reduction of hepatic cholesterol production, in hypercholesterolemia (Murakami et al 2010); and reduction of caspase-8 and -9, in ischemic neuronal apoptosis (Taranukhin et al 2008). Some of these mechanisms depend, at least in part, on the antioxidant actions of taurine (Penttila 1990;Xiao et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…The mechanisms involved on its actions range from increasing insulin secretion (Ribeiro et al 2009) and action ), in diabetes; reduction of hepatic cholesterol production, in hypercholesterolemia (Murakami et al 2010); and reduction of caspase-8 and -9, in ischemic neuronal apoptosis (Taranukhin et al 2008). Some of these mechanisms depend, at least in part, on the antioxidant actions of taurine (Penttila 1990;Xiao et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Taurine inhibits ischemia-induced apoptosis in rat neonatal cardiomyocytes by prevention of apoptosome assembly, cleavage and activation of caspase-3/-9 [20,21]. In mouse hypothalamic nuclei taurine reduced ischemia-induced caspase-8 and caspase-9 expression thus attenuating apoptosis [22]. It has been reported that in rat testes, pre-treatment with taurine, suppressed arsenic-induced activation of caspase-3 thus suppressing apoptosis [23].…”
Section: Cell-protective Roles Of Taurinementioning
confidence: 99%
“…This effect is manifested by attenuation of platinum (cisplatin) accumulation [24], suppression of the activation of caspase-3 [36], reduction in caspase-8 and caspase-9 expression [22], prevention of caspase-3/-9 cleavage and assembly of the apoptosome [20,21], as well as inhibition of DNA fragmentation and apoptotic cell shrinkage [25]. We find that neither taurine enrichment nor taurine depletion have any effect on the cisplatininduced caspase-3 activity, i.e., cellular taurine does not rescue EATC from cisplatin-induced apoptosis.…”
Section: Taurine and Taut In Cisplatin Resistancementioning
confidence: 99%
“…In the ischemic hypothalamic nucleus of mice, taurine also attenuated the expression of caspase-8 and caspase-9 (Taranukhin et al 2008 ;Leon et al 2009 ) .…”
Section: Discussionmentioning
confidence: 89%